Stock market valuation in the United States - Patrick Bisciari; Alain Durré; Alain Nyssens (National Bank of Belgium, 2003)
This paper gives an overview of some issues related to market valuation, focusing on the developments on the New York equity markets. The 42.4 p.c. fall in the S&P 500 price index between 24 March 2000 - when it reached its all-time high - and 31 December 2002 is situated in a very long term perspective. It then appears that some bear markets were more pronounced in the past but that the bull market preceding the 2000-2002 bear market had been particularly long and impressive in extent. Given this sharp correction, we will discuss whether the S&P 500 was correctly valued at the end of 2002. To this end, we make use of valuation indicators defined as the ratio of the price to a fundamental. The fundamentals considered here are, according to the discount dividend model, annual earnings and, according to Q-theory, net worth. In December 2002, price-earnings (P/E) still showed a significant overvaluation of equity prices when compared to the historical average over the 1871-2002 period but, since July 2002, the overvaluation has not been significant in the case of Q. The evidence is even more mixed when the comparison is made, for each valuation indicator, with their average over the last 10 years. Simulations based on VAR models for P/E and Q were carried out to check whether, on two occasions, the S&P 500 in real terms climbed to a level perceived as irrational given past experience, implying that a correction had to be expected. These occasions were the so-called 1929 and 2000 bubbles. The models showed that, at some point in time before the peak in (real) stock prices was reached, the real S&P 500 exceeded the upper band of the 95 p.c. confidence intervals during both periods. For each of them, the Q model showed earlier and more persistent signals of significant overvaluation of stock prices than for the P/E model. Finally, in December 2002, both models indicated that the stock price had come back largely within the confidence interval.
Keywords: G10; C32; C53; 330; stock market; financial market; united states; stock prices forecast; Aktienindex; Börsenkurs; Spekulationsblase; USA